Phyto-response effects of moringa oleifera leaves (moringa oleifera) ethanol extract on osteoblast and mandibular bone osteoclasts (rattus norvegicus) (experimental study using histopathology fluorescent light) - Basri A. Gani; Munifah Abdat; Salwa D. Kariza; Chairunas (Journal of Dentomaxillofacial Science, 2020)
Objective: To determine the phyto-response effect of the Kelor leaves ethanol extract (Moringa oleifera) in osteoblasts and osteoclasts cells of rat mandibular bones (Rattus norvegicus) in the atmosphere of fluorescent light histopathologically. Material and Methods: Manufacture of Kelor leaf ethanol extract by maceration method and ethanol 96%.  The 10-tailed mice are divided into 1 mouse-tails that are only exposed to light, 3-tailed mice positive groups given the drug vitamin D, 3-tails of negative group rats given aquades, and 3-tails of treatment given the leaf ethanol extract. The treatment of rats was carried out on the 0 day, 7th Day, 14th and 21st days, then dieutanasia using ether anesthesia and carried out the cutting of the mandibular bone using bone, fixation, decalcification to the calculation of cells osteoblasts and osteoclasts with a microscope (Olympus BX-51) 400X magnification. Results: There was a significant difference between the positive control group, the negatives and the treatment group that applied the Kelor leaf ethanol extract to the rat mandibular bone and exposed to light for 24 hours. The treatment group applied the Kelor leaf ethanol extract has the highest number of osteoblasts cells on day 28. Conclusion: The Kelor leaf ethanol extract is effective in stimulating the osteoblasts cells of the bones that have been exposed to light in the long term. The Kelor leaf ethanol extract can balance the bone growth cycle significantly over vitamin D.